An In-Depth Analysis of the Contribution of the Human Development Index and Labor Force to the Gross Regional Domestic Product in Regencies/Cities of Jambi Province - Azizah Al Munawaroh; Viola Novaryca; Anggun Putri Amelia; Eliyana; Amelia Yustria (IECON: International Economics and Business Conference, 2025)
This research is entitled "The Influence of the Human Development Index and Labor Force on the Gross Regional Domestic Product of Regencies/Cities in Jambi Province". The first aim of this research is to determine and analyze the development of the human development index, labor force and GRDP in Jambi Province. Second, to determine and analyze the influence of the human development index and workforce on district/city GRDP in Jambi Province. The research method used was secondary data analysis with quantitative methods using 11 districts/cities in Jambi Province. Multiple linear regression analysis tool using panel data with the help of the Eviews application.   The results of the analysis concluded that the first is that the human development index for districts/cities in Jambi Province has an overall average of 71.76 percent with Jambi City having the highest HDI, namely 79.35 percent higher than the overall HDI. Meanwhile, East Tanjung Jabung Regency has the lowest HDI with an HDI below the overall HDI average, namely 66.95 percent. For the district/city workforce in Jambi Province, the overall average increased by 1.07 percent or 166,549 people, with the highest increase occurring in Muaro Jambi Regency with the average increase above the overall increase in the workforce, namely 2.92 percent. Meanwhile, West Tanjung Jabung Regency, on average, the workforce decreased by -0.77 percent. And the gross regional domestic product of districts/cities in Jambi Province as a whole increased by an average of 3.38 percent with the highest increase occurring in Batanghari Regency with an average increase in gross regional domestic product of 5.09 percent and the lowest occurring in the Regency. East Tanjung Jabung with an increase in gross regional domestic product of 0.73 percent during the 2018-2023 period. Second, partially using FEM panel data, only the human development index (HDI) has a significant effect on increasing gross regional domestic product in the 2018-2023 period. Meanwhile, the labor force (AK) does not have a significant effect on increasing the gross regional domestic product of districts/cities in Jambi Province. With the highest increase in gross regional domestic product if the human development and labor force index remained constant, it occurred in West Tanjung Jabung Regency and the lowest in Kerinci Regency. With a high level of confidence, HDI and AK influence district/city GRDP by 99.25 percent.